188k views
3 votes
3(x + 1) = -2(x - 1) + 6.

2 Answers

4 votes

Answer:

x = 1

Explanation:

Step 1: Simplify both sides of the equation.

3(x+1)=2(x−1)+6

(3) (x )+ (3) (1) = (2) (x) + (2) (−1) + 6 (Use Distrbutive Property)

3x + 3 = 2x + (−2) + 6

3x + 3 = (2x) + (−2 + 6) (Combine Like Terms)

3x + 3 = 2x + 4

3x + 3 = 2x + 4

Step 2: Subtract 2x from both sides.

3x + 3 − 2x = 2x + 4 − 2x

x + 3 = 4

Step 3: Subtract 3 from both sides.

x + 3 − 3 = 4 − 3

x = 1

User Nikolay Dyankov
by
5.6k points
4 votes
X=1 it’s this lmk if you get right
User Lostintranslation
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.